PERFORMANCE EVALUATION IN PT PLN EAST JAVA DISTRIBUTION USING SUSTAINABILITY BALANCED SCORECARD (BSC) - Sakti, Anisa Hardian (Jurnal Ilmiah Mahasiswa FEB, 2018)
Sustainability Balanced Scorecard is a strategy management system that has been developed to focus on aspects based on Balanced Scorecard. The measurement of corporate performance using Sustainability Balanced Scorecard method is seen from five perspectives, which are financial perspective, customer perspective, internal business process perspective, perspective of learninggrowth perspective, and social perspective. The type of research used is qualitative with descriptive research method. The results of data processing show that based on financial perspective included in quite successful category, based on customer perspective included in has not been quite successful category, based on internal business process perspective included in good category, based on learning-growth perspective included in success category, and based on social perspective included in success category. Analysis of performance measurement results at PT.PLN (Persero) Distribution East Java included into good category although not yet stable, because in each perspective still found some indicators still has not reached the expected target. So it can be concluded that PT. PLN (Persero) Distribution East Java has been quite successful in terms of performance achievement. Key Words: financial perspective, customer perspective, internal business process perspective, perspective of learning-growth perspective, social perspective